Malta : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
Malta has advanced toward accession to the European Union (EU), and its progress in international competition and fiscal deficit reduction has contributed to rapid growth and enhanced the economy's resilience to economic shocks. Executive Directors stressed the need for fiscal consolidation, strengthening of public finances, monetary, and exchange rate policies and the banking system. They welcomed the authorities' efforts in antimoney laundering and the combating of the financing of terrorism, and urged the authorities to criminalize the financing of terrorism.